Fitting a Model to Students' Cognitive engagement: A Step Towards Accountable Education in Medical Education - Mehrdadian, Parisa (2021)
Introduction: Motivation is one of the most important effective factors in learning. It can lead to long-lasting learning in connection with identity. Creating an appropriate setting for development and actualization of students with different Scientific, social and cultural abilities is one of the accountable education package’s The Health System Evaluation Plan. Whereas emotion regulation and management is one of the important needs of students and empowering them in this field is a necessity. Method: Present study is a kind of non-experimental design. To speak more precisely, it is a type of correlations design which has analyzed a structural pattern of variables relationship, done in 2016 in Sabzevar university of medical Sciences, 720 students was selected using multistage cluster sampling as  the sample group  and employed Berzonsky’s identity style Inventory (ISI-3), achievement goals scale of Midgley et al(PALS), and motivated strategies for learning questionnaire (MSLQ). Data was analyzed using path analysis. Results: nformational identity style has both direct and indirect effect (through the intervening role of mastery goals) on cognitive engagement (P<0.01). Normative identity style has an effect The path from diffuse-avoidant identity style to performance-avoidance goals was excluded from fitted model, fitted model predicts 41% of cognitive engagement. Conclusion: Inorder to improve learning, cognitive engagement (mental efforts) can be targeted using motivational and identity variables.